High resolution thermal and multispectral remote sensing for detecting devitalized trees in Monarch Butterfly Biosphere Reserve - Guadarrama-León, Ramón; Sáenz-Romero, Cuauhtémoc; Rosas-Chavoya, Marcela; Méndez-Montiel, José T.; Lindig-Cisneros, Roberto A.; Blanco-García, Arnulfo; Gallardo-Salazar, Jose Luis (Forest Systems, 2026)
Aim of study: To identify different levels of devitalization in individuals of Abies religiosa (Kunth) Schltdl. & Cham. (oyamel) in the core zone of the Monarch Butterfly Biosphere Reserve (MBBR), using multispectral and thermal information captured with drone.Area of study: The study area, comprising 26 ha, is located within the federal property of the MBBR. This area also belongs to the core zone of the Protected Natural Area.Material and methods: Overflights were conducted with drones equipped with multispectral and thermographic sensors in monitoring plots. Using high-resolution images captured by drone and photogrammetric processing, the normalized difference vegetation index (NDVI), surface temperature (ST), and temperature-vegetation dryness index (TVDI) were calculated. These values were combined with field data to determine three different levels of tree devitalization (i.e., healthy, devitalized, and dead trees).Main results: The results demonstrated that this technology can be used to statistically distinguish the different levels of devitalization in oyamel individuals.Research highlights: This is the first research in Mexico that use Thermal and Multiespectral high resolution information related with field data applied to Abies religiosa and provides a methodological precedent for identify forest decline symptoms.